Should we care about coexistence in L4S? Assessing round-trip time significance and low-latency for all - Freitas, Eduardo; Veras, Maria Eduarda; Oliveira Filho, Assis T. de; Kelner, Judith; Sadok, Djamel (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The L4S architecture promises to resolve the throughput-latency trade-off, yet concerns regarding its coexistence with classic TCP persist. The literature presents experimentations on how L4S flows can potentially starve non-L4S ones when deployed on networks with incomplete or no support for L4S, an already known fact. However, few works assess the L4S performance considering networks with full support for it. This work evaluates the dynamics of L4S performance on networks that fully support it and assesses that coexistence is no longer a concern and could also be considered architecturally resolved. We demonstrate that classic flows retain fair throughput with L4S flows but suffer self-inflicted queuing delays exceeding 15 ms, deteriorating their RTT.